2019
DOI: 10.1080/13102818.2019.1638301
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of nitrogen-fixingKlebsiella variicolaGN02 expression vector pET28a-Lac-EGFP and its colonization ofPennisetum giganteumz.x.lin roots

Abstract: To explore the colonization of endophytic nitrogen-fixing bacterium Klebsiella variicola in Penniseum sinense, pET28a and the enhanced green fluorescent protein (EGFP) were used as basic elements to construct a recombinant expression vector pET28a-Lac-EGFP with the addition of starter Lac in pUC18 vector using enzymatic digestion and splicing methods. The constructed recombinant vector was transformed into K. variicola GN02 cells with electroporation method and the colonization of EGFP-tagged K. variicola GN02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The total nitrogen content of C. fungigraminus may exceed its total nitrogen uptake from soil and fertilizer, presumably because of the endophytic nitrogen-xing bacteria. It's found that Klebsiella and Bradyrhizobium being the main nitrogen-xing bacteria present in C. fungigraminus's roots and stems at Hainan province (Lin et al 2019). In this study, we intend to evaluate the diversity and abundance of nitrogen-xing bacteria in rhizosphere of C. fungigraminus in Hainan, as well as screening the main PGPR to explore the promotion effect on C. fungigraminus seedlings and soil.…”
Section: Introductionmentioning
confidence: 99%
“…The total nitrogen content of C. fungigraminus may exceed its total nitrogen uptake from soil and fertilizer, presumably because of the endophytic nitrogen-xing bacteria. It's found that Klebsiella and Bradyrhizobium being the main nitrogen-xing bacteria present in C. fungigraminus's roots and stems at Hainan province (Lin et al 2019). In this study, we intend to evaluate the diversity and abundance of nitrogen-xing bacteria in rhizosphere of C. fungigraminus in Hainan, as well as screening the main PGPR to explore the promotion effect on C. fungigraminus seedlings and soil.…”
Section: Introductionmentioning
confidence: 99%